2020
DOI: 10.1029/2019pa003685
|View full text |Cite
|
Sign up to set email alerts
|

Multiproxy Reduced‐Dimension Reconstruction of Pliocene Equatorial Pacific Sea Surface Temperatures

Abstract: A controversial aspect of the Pliocene climate system is a posited permanent sea surface temperature (SST) distribution resembling that during El Niño events, which is largely inferred from sea surface temperatures reconstructed from several sites in the equatorial Pacific. We utilize a reduceddimension methodology on a compilation of previously published multiproxy (Mg/Ca, U k′ 37 , TEX 86 , and foraminifer assemblages) Pliocene SST records from the equatorial Pacific to reconstruct spatial and temporal snaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 140 publications
0
18
0
Order By: Relevance
“…In the other approach, one virtually ignores taxonomy and uses only the physiognomic characteristics of different taxa (without assigning them names), including sizes and shapes of the plant organs. Most commonly, leaves are used (e.g., Spicer et al, 2009Spicer et al, , 2011Wolfe, 1993Wolfe, , 1995. Investigators first estimate the fractions (percentages) of the many characteristics in fossil assemblages, like leaves with (or without) teeth or sizes, within a given range.…”
Section: ■ Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In the other approach, one virtually ignores taxonomy and uses only the physiognomic characteristics of different taxa (without assigning them names), including sizes and shapes of the plant organs. Most commonly, leaves are used (e.g., Spicer et al, 2009Spicer et al, , 2011Wolfe, 1993Wolfe, , 1995. Investigators first estimate the fractions (percentages) of the many characteristics in fossil assemblages, like leaves with (or without) teeth or sizes, within a given range.…”
Section: ■ Approachmentioning
confidence: 99%
“…Such differences tend to be greater at high than low latitudes, and therefore even if the mean temperature of Earth at 15-3 Ma was, for example, 3 °C warmer than today, that greater warmth seems likely to have been smaller, and perhaps negligible in the Eastern Cordillera. Before 4-3 Ma, however, the eastern tropical Pacific Ocean was warmer than today by ~4 °C, as it is during major El Niño events (e.g., Dekens et al, 2007;Lawrence et al, 2006;Ravelo et al, 2006;Wara et al, 2005;Wycech et al, 2020). Assuming that modern El Niño teleconnections apply to past climates, the Sabana de Bogotá before 4-3 Ma would have been warmer by ~2 °C than today (Pérez-Angel and Molnar, 2017).…”
Section: ■ Caveatsmentioning
confidence: 99%
“…Recent data compilations show that the exact magnitude of the reconstructed Pliocene temperature gradient depends on the time window within the Pliocene selected for comparison, which proxy data is used and how they are analyzed (McClymont et al, 2020). Nonetheless, there is agreement that the equatorial temperature gradient was reduced during the Pliocene (Tierney, Haywood, et al, 2019;Wycech et al, 2020), mainly because there is unequivocal evidence that the East Pacific cold tongue was considerably warmer than today in the Pliocene. Thus, the debate centers on data from the west, specifically, the Mg/Ca-based evidence that indicates that the IPWP was not warmer than today in the Pliocene (Wara et al, 2005).…”
mentioning
confidence: 99%
“…However, modern-like SSTs for the early Pliocene WPWP are suspect given that these previous foraminifer Mg/Ca-derived records did not account for Pliocene Mg/Ca sw ratios and the fact that U k' 37 is an imprecise paleothermometer at temperatures greater than 30°C (Tierney and Tingley, 2018). These discrepancies notwithstanding, we note that the Pliocene SST record presented in this study for Site 806 (revised from Wara et al, 2005) was included in a recent statistical multi-proxy reconstruction of equatorial Pacific SSTs (Wycech et al, 2019). The study concluded that the Pliocene west-east SST difference was reduced by 4.4°C relative to the recent (0-0.5 Ma) average, which is consistent with El Padre conditions during the early Pliocene.…”
Section: Implications For the El Padre Controversymentioning
confidence: 68%
“…The redistribution of moisture in the modern equatorial Pacific is governed by Walker atmospheric circulation, which imparts an asymmetric zonal (E-W) precipitation gradient with wetter conditions in the west relative to the east (Bjerknes, 1969). However, several previous studies have posited that El Niño-like conditions, termed "El Padre" (Ravelo et al, 2014), prevailed across the equatorial Pacific during the early Pliocene as evidenced by a weakened zonal SST gradient and a deeper thermocline in the east Pacific (Cannariato and Ravelo, 1997;Chaisson and Ravelo, 2000;Dekens et al, 2008;Ford et al, 2015;Lawrence et al, 2006;Molnar and Cane, 2002;Philander and Fedorov, 2003;Ravelo et al, 2006;Seki et al, 2012;Wara et al, 2005;Wycech et al, 2019).…”
mentioning
confidence: 99%